2008
DOI: 10.1161/strokeaha.107.508754
|View full text |Cite
|
Sign up to set email alerts
|

Oxyhemoglobin-Induced Expression of R-Type Ca 2+ Channels in Cerebral Arteries

Abstract: Background and Purpose-Cerebral vasospasm after subarachnoid hemorrhage (SAH) is a major contributor to mortality and morbidity following aneurysm rupture. Recently, R-type voltagedependent Ca 2+ channel (VDCC) expression has been associated with increased cerebral artery constriction in a rabbit model of SAH. The goal of the present study was to examine whether the blood component oxyhemoglobin (oxyHb) can mimic the ability of SAH to cause R-type VDCC expression in the cerebral vasculature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 36 publications
1
18
0
1
Order By: Relevance
“…For example, Timothy E, et al . demonstrated that the hemoglobin contributes to excessive cerebral artery constriction following SAH18. After the incubation of hemoglobin with VSMC to mimic neuropathology of SAH, our results firstly revealed that hemoglobin pretreatment could also lead to cerebral VSMC phenotypic switch, causing dramatic downregulation of contractile proteins and overexpression of synthetic proteins in VSMC, consistent with the animal observation following SAH.…”
Section: Discussionsupporting
confidence: 79%
“…For example, Timothy E, et al . demonstrated that the hemoglobin contributes to excessive cerebral artery constriction following SAH18. After the incubation of hemoglobin with VSMC to mimic neuropathology of SAH, our results firstly revealed that hemoglobin pretreatment could also lead to cerebral VSMC phenotypic switch, causing dramatic downregulation of contractile proteins and overexpression of synthetic proteins in VSMC, consistent with the animal observation following SAH.…”
Section: Discussionsupporting
confidence: 79%
“…Despite expression of Ca V 2.1 across species, functional differences in channel function are evident: ω-agatoxin dose-dependently inhibits K + -induced constriction in human but not murine intrarenal arteries (552). In cerebral arteries expression and function of R-type VGCCs (Ca V 2.3) appears after exposure to oxyhemoglobin as occurs during hemorrhagic stroke, contributing to the vasospasm that often occurs after this type of cerebrovascular accident (879). …”
Section: Voltage-gated Ca2+ Channelsmentioning
confidence: 99%
“…Several authors suggest that the functional significance of R-type channels may lie within small diameter blood vessels and that blood vessels of different sizes are impacted differently by SAH [58]. Furthermore, exposure of organ cultured rabbit cerebral arteries to oxyHb induces the expression of R-type VGCC mRNA in small vessels rendering the vessels sensitive to SNX-482 (R-type antagonist) and less sensitive to diltiazem [59]. SNX-482 was also found to attenuate CBF reduction after SAH in rats [60].…”
Section: Changes In Ion Channel Expression and Function In Delayedmentioning
confidence: 99%